Seawater as Alkali Activator in Fly Ash Based Geopolymer - Andrie Harmaji (Bina Nusantara University, 2022)
Indonesia as a maritime country in the world with 66% of its territory consists of maritime territory. A lot of potential that can be exploited, such as sea water. XRD characterization results indicate that the sea water from Tanjung Priok, North Jakarta, Indonesia has a compound Halite (NaCl) and Bassanite (CaSO4.5H2O) in the salt form. These compounds are alkaline thereby can influence the compressive strength of the geopolymer. Geopolymer is made up of aluminosilicate precursors which are activated by the alkaline activator solution, which usually combines sodium silicate and sodium hydroxide. The precursor material is waste from the coal based power plant called fly ash that produce 219.000 tonne per year and still underutilized but potentially as an alternative to cement. In this study, seawater was used to substitute the sodium hydroxide in alkali activator as an effort to reduce the manufacturing cost of Geopolymer. Geopolymer prepared by mixing fly ash as a precursor, silica sand as aggregates, with activator, then casted and cured by immersion. After 28 days compression test was conducted to measure the strength of resulting geopolymer. The sample consisted of a mixture of fly ash, silica sand, waterglass, and seawater produces strength of 16.60 MPa. X-Ray Diffraction characterization was conducted to study the compound formed from precursors activated with seawater alkali activator. Resulting diffractogram indicate the formation of anorthite compound as proof of Geopolymerization has been successfully occured.